(2u-3)(6+u)=0

Simple and best practice solution for (2u-3)(6+u)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2u-3)(6+u)=0 equation:



(2u-3)(6+u)=0
We add all the numbers together, and all the variables
(2u-3)(u+6)=0
We multiply parentheses ..
(+2u^2+12u-3u-18)=0
We get rid of parentheses
2u^2+12u-3u-18=0
We add all the numbers together, and all the variables
2u^2+9u-18=0
a = 2; b = 9; c = -18;
Δ = b2-4ac
Δ = 92-4·2·(-18)
Δ = 225
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{225}=15$
$u_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(9)-15}{2*2}=\frac{-24}{4} =-6 $
$u_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(9)+15}{2*2}=\frac{6}{4} =1+1/2 $

See similar equations:

| 75+5x=6x-5 | | 6d−5d=12 | | 18+x=19 | | 53+39=4+7x | | g–4+ –2=–6 | | 8x=61 | | 23-2x=-5+4(x+4) | | 3x–49=32 | | 5+(5+3x)=35 | | 9/5x-1/6=-1 | | 2xx-7=-23 | | 45=52+x | | 2x-2/6=-6 | | –8−6r=–7r | | 7n+7=8n | | 3x12=x4 | | 100+8x=800 | | 2=x-6*x | | 25-4n=-5(n-4) | | 2=x-6•x | | 10+27x−9x=10+18x | | 84=5x+3x+4 | | x–28=34 | | 3x-7(x+5)=-35 | | 2m-44=76-8 | | 5x-3x+7=3x+4x-3 | | 29=w/2+12 | | 60+80=x+50 | | 3x=2/5=4 | | 8x-30=26 | | w/3+15=37 | | 16=35+2t |

Equations solver categories